Utilizing Augmented Reality-Based Learning Media on Concrete Compressive Strengt Test Tool (Universitas Negeri Semarang, 2022)
Augmented Reality is a technology that can incorporate virtual objects in two or three dimensions into a real environment in real time. In the current Industrial Revolution 4.0 era, AR technology is widely used in the fields of games, medicine, and image processing, while it is rarely used in the field of education. The purpose of the present study is (1) to describe the process of developing learning media based on Augmented Reality in material technology course. (2) to produce learning media based on Augmented Reality on concrete compressive strength test material that is valid, practical, and effective. This type of research is research and development (RD). The development process refers to the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The results showed that the average validity score of Augmented Reality-based learning media about concrete compressive test was 4.51 in the very valid category. Based on student response data, it showed that students had a positive response to the augmented reality-based learning media on concrete compressive strength test, showing a minimum of 89.96% or more students responding in the agree category, for each aspect that was responded to. Around 95.44% of students were able to achieve the value of learning completeness criteria so that the Augmented Reality-based learning media was categorized as effective.